2002
DOI: 10.1007/s00464-001-9150-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic fenestration of posttransplant lymphoceles

Abstract: Laparoscopic lymphocele fenestration is reserved for patients in whom temporary drainage with or without sclerotherapy failed to resolve the fluid collection. In these cases the laparoscopic approach offers obvious technical and clinical advantages compared to open operative techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 46 publications
1
29
0
4
Order By: Relevance
“…Open lymphocelectomy has long been the standard. A literature review including 129 patients who underwent open drainage between 1980 and 1998 revealed a complication rate of 4% and a recurrence rate of 15% (18). It is believed that the high incidence of symptomatic recurrences following open drainage is a result of bowel adhesions obstructing the internal window and thus causing extraperitoneal fluid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Open lymphocelectomy has long been the standard. A literature review including 129 patients who underwent open drainage between 1980 and 1998 revealed a complication rate of 4% and a recurrence rate of 15% (18). It is believed that the high incidence of symptomatic recurrences following open drainage is a result of bowel adhesions obstructing the internal window and thus causing extraperitoneal fluid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…This easy-to-perform method reveals high effectiveness [4]. It involves creating a gap in the peritoneum, which establishes communication between the lymphocele and the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…sclerotherapy, puncture, external drainage [1,4,5,7]. Puncture and external drainage are not recommended in the case of large lymph collection due to a high risk of possible infection and recurrence [4,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a well-recognized complication of renal transplantation, with incidence rates up to 20% [2]. Although small lymphoceles may remain undetected, larger ones can manifest as lower abdominal masses, ipsilateral lymphedema, continued incisional drainage, fever, weight gain, and tenderness in the iliac fossa [4,11,12].…”
mentioning
confidence: 99%